Photosynthesis Control: An underrated short-term regulatory mechanism essential for plant viability. (2nd April 2016) - Colombo, Monica; Suorsa, Marjaana; Rossi, Fabio; Ferrari, Roberto; Tadini, Luca; Barbato, Roberto; Pesaresi, Paolo
ABSTRACT: Regulation of photosynthetic electron transport provides efficient performance of oxygenic photosynthesis in plants. During the last 15 years, the molecular bases of various photosynthesis short-term regulatory processes have been elucidated, however the wild type-like phenotypes of mutants lacking of State Transitions, Non Photochemical Quenching, or Cyclic Electron Transport, when grown under constant light conditions, have also raised doubts about the acclimatory significance of these short-regulatory mechanisms on plant performance. Interestingly, recent studies performed by growing wild type and mutant plants under field conditions revealed a prominent role of State Transitions and Non Photochemical Quenching on plant fitness, with almost no effect on vegetative plant growth. Conversely, the analysis of plants lacking the regulation of electron transport by the cytochrome b 6 f complex, also known as Photosynthesis Control, revealed the fundamental role of this regulatory mechanism in the survival of young, developing seedlings under fluctuating light conditions.